Investigating Impulse Buying Behavior in Live Streaming Shopping with SOR Model Perspective - Widyastuti, Pristiana (SAFE-Network, 2023)
This research aims to investigate impulse buying behavior in live-streaming shopping with SOR Model Perspective. This research is conducted using a quantitative approach and statistical tests. The research method uses the Structural Equation Model (SEM). The statistical tool is using SmartPLS. The sampling technique uses non-probability with a purposive sampling approach based on certain criteria, Indonesian people who have watched and bought products online via live streaming. To collect samples from an infinite population, the sample size was determined to be 96 respondents. The study results reveal that online purchasing behavior on live-streaming platforms is stimulated by interactivity factors. Interactive experiences can increase the desire to immediately own the product or service. Hedonic and utilitarian can mediate impulse buying in live-streaming shopping. Viewers are captivated by products or services that provide aesthetic satisfaction (hedonic) or functional solutions (utilitarian) and impulsively buy because of the visual or emotional impact of live-streaming